Território e poder : o orçamento participativo como política territorial de governo em Alagoinhas/BA (Brasil) - Cruz Neto, Claudemiro Ferreira da (2005)
This work looked for to investigate the subject of the budget participatory under the optics of the materialism dialectics, leaning for the notion of territorial politics as government's action, gone back to the exercise and the maintenance of the power, and of the civil society in the perspective of the autonomy. The used methodology was dialectics essentially, being been worth of the technique of analysis of discursive content and of information represented primary and secondary graph and cartographically. It was used for so much of interviews, questionnaires and participant observation in linked events to the dynamics of the budget participatory with the objective of lifting the history of the construction and implantation of this administration instrument, in Alagoinhas, Bahia (Brazil), as well as the methodology used to assure him/it as a participation instance that walked in the direction of the direct democracy and of the construction of the autonomy. The time and the space were considered while specific theoretical-methodological subjects of the geographically of the analysis. The developed research also allowed the perception of as the budget participatory it is seen by the executive power while government's politics that relates space and power starting from the notion of territorial politics. Besides, it was possible to identify as the population he/she also wraps up with the discussion of the budget participatory and which the possibilities of this administration instrument to change in an effective mechanism in the conquest of the solemnity-administration for the popular masses, inside, of course, of the marks of the capitalist sociability and face to the established objectives for the municipal executive coordinated by the PT - Party of the Workers.